Serum lipid levels in patients with periodontal disease: A meta-analysis and meta-regression - Nepomuceno, Rafael [UNESP]; Pigossi, Suzane C. [UNESP]; Finoti, Livia S.; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Barros, Silvana P.; Offenbacher, Steven; Scarel-Caminaga, Raquel M. [UNESP] (Wiley, 2017)
Aim: Several papers have considered the potential relationship between periodontitis and lipid parameters. The present systematic review, meta-analysis and meta-regression studies focused on investigating whether serum lipid parameter levels were elevated in patients with periodontal disease (PD; without altered systemic conditions) in comparison with periodontally healthy subjects. Materials and Methods: Eligible studies were those with data about serum lipid parameter levels in non-smoking subjects with and without chronic periodontitis, who are generally healthy and not taking any medication for dyslipidaemia. Mean differences and 95% confidence intervals for total cholesterol, triglycerides, low-density lipoprotein (LDL) cholesterol and high-density lipoprotein (HDL) cholesterol were obtained from all the selected studies. Results: A total of 19 publications were included for meta-analysis. Participants with chronic periodontitis presented significantly higher serum levels of LDL and triglycerides (p =.003 and p <.0001, respectively). The total cholesterol was higher in the PD group, but without significant difference in comparison with healthy participants. Significantly (p =.0005) lower HDL serum levels were found in patients with chronic periodontitis than in healthy subjects. Conclusions: Even considering the limitations of this meta-analysis, it is suggested that PD is significantly associated with reduction in HDL and elevation of LDL and triglyceride concentrations. This analysis supports the rationale that periodontal disease is associated with lipid metabolic control.
Keywords: cholesterol; dyslipidaemia; high-density lipoprotein cholesterol; low-density lipoprotein cholesterol; periodontal disease; triglycerides